MANUSKRIP MUSHAF AL-QUR'AN PONDOK PESANTREN JOGOREKSO MAGELANG: Studi Kodikologi dan Qira'at - Wanodya, Ajeng Pudyastuti Budi (AL ITQAN: Jurnal Studi Al-Qur'an, 2021)
This research examines the manuscripts of the Qur'anic mushaf at the Jogorekso Islamic Boarding School in Gunungpring Magelang by focusing on the aspects of codicology and qirā'at. The Mushaf of the Qur'an at the Jogorekso Islamic Boarding School, Gunungpring, Magelang itself is a manuscript that has been passed down from generation to generation. This Qur'anic manuscript is from the 19th century. The manuscript contains the text of the Qur'an from surah al-Fātiḥah to surah al-Nās. The researcher describes the physical manuscripts using a philological approach, namely codicology and textology. The type of paper used is European paper, as evidenced by the visible light, thick lines and thin lines, and watermarks and countermarks. This manuscript has plant-based and geometric illuminations in three parts, namely the beginning, middle and end. Illumination is also found in every surah in the name of a rectangular sura, also in each juz which is located on each right of the mushaf page which is in the form of a circle with various shapes that tend to be inconsistent. In addition, there are also verse symbols, punctuation marks, recitation signs, and ruk'. The study of qirā'at applied in surah al-Kahf found differences in qirā'at in fifty-five verses and the manuscripts of the Qur'anic manuscripts at the Jogorekso Islamic Boarding School in Gunungpring Magelang have various qirā'at.